Animal migration optimization algorithm: novel optimizer, analysis, and applications - Abualigah, Laith (2024)
A new heuristic optimization algorithm was proposed in 2013 called the animal migration optimization (AMO) algorithm. It is based on the animal actions and habits in migration seasons. Optimization algorithms are applied to find the optimal solutions in many domains and fields such as image processing, machine learning, and others. In this paper, we present an overview of the AMO algorithm, describe the algorithm procedure, summarize some of the recent works and applications that use AMO algorithms, classify these works in many application domains, and display the robustness points, weak points, and limitations for AMO. This paper can help and direct the researchers in future works in using AMO in their studies.